(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
Folklore has always been an integral part of the cultural identity of people, providing a rich repository of images, symbols, and themes for poets and writers. In Karakalpakstan, folklore occupies a central place in the cultural identity of its people. Ibragim Yusupov is one of the most prominent contemporary poets and songwriters from Karakalpakstan, whose works are characterized by a strong connection to the region’s cultural heritage. His lyrics often feature references to traditional motifs and symbols, such as mountains, rivers, animals, and plants, which are used to convey complex emotions and ideas. This study aims to explore the ways in which Yusupov reinterprets and transforms the cultural heritage of his region, creating a new poetic language that reflects both the continuity and innovation in Karakalpak folklore.